O uso dos derivativos financeiros como estratégia de proteção de preço aplicado pelas usinas de cana-de-açúcar do Estado de São Paulo, no período de 2003 a 2009 - Jacob, Renato Manga (2010)
This study attempted to evaluate financial strategies for risk reduction used by 17 sugar mills located in the State of São Paulo, for the protection of price and exchange rate over the period 2003 to 2009. The methodology was based on field research, in addition to collecting information on the associations connected to this segment. The application of the questionnaire was an attempt to assess empirically how they act with derivatives. This questionnaire included questions about risk management, type of derivatives used and procedures of the plants as their engagement in the period 2003 to 2009. The sample surveyed, only two companies did not answer the questionnaire. However this did not compromise the objective of the research, which was to map out the strategies of these plants with regard to protection against exchange rate and price of sugar. The focus of this research in relation to price the product was sugar, because it is a commodity with great relevance in Brazilian economy, which the country is the largest producer and exporter of this commodity. The results obtained in this study suggest that the interviewed companies operate similarly with respect to price protection and exchange, but they could invest more resources to obtain better results, such as area specialists and technical support, given the importance of this management in the financial result